2019
DOI: 10.1002/slct.201803370
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of 2‐Amino‐thiophene‐proline‐conjugates and Their Anti‐tubercular Activity against Mycobacterium Tuberculosis H37Ra

Abstract: The emergence of extensively drug resistant tuberculosis (XDR‐TB) and multi‐drug resistant tuberculosis (MDR‐TB) has necessitated the development of new drugs with short chemotherapy treatment regime and cost effectiveness. To overcome these challenges, we are reporting the synthesis of a series of 2‐amino‐thiophene‐proline‐conjugates which show potent in‐vitro and ex‐vivo anti‐tubercular (anti‐TB) activity against mycobacterium tuberculosis (mtb) H37Ra. The synthesis of these 2‐amino‐thiophene‐proline‐conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…With the aim of developing new chemo types, in 2019, Baravkar et. al investigated a series of dipeptides (Figure ), in which different amino acids were tethered to the 2-aminothiophene ring . Derivatives containing the proline (Pro) residue were the most promising and were reported as a new class of tuberculosis inhibitors with potent in vitro and ex-vivo anti-TB activity against both active and dormant Mtb H37Ra (Table ).…”
Section: Medicinal Chemistry Efforts Toward the Development Of Novel ...mentioning
confidence: 99%
See 1 more Smart Citation
“…With the aim of developing new chemo types, in 2019, Baravkar et. al investigated a series of dipeptides (Figure ), in which different amino acids were tethered to the 2-aminothiophene ring . Derivatives containing the proline (Pro) residue were the most promising and were reported as a new class of tuberculosis inhibitors with potent in vitro and ex-vivo anti-TB activity against both active and dormant Mtb H37Ra (Table ).…”
Section: Medicinal Chemistry Efforts Toward the Development Of Novel ...mentioning
confidence: 99%
“…al investigated a series of dipeptides (Figure 19), in which different amino acids were tethered to the 2-aminothiophene ring. 246 Derivatives containing the proline (Pro) residue were the most promising and were reported as a new class of tuberculosis inhibitors with potent in vitro and ex-vivo anti-TB activity against both active and dormant Mtb H37Ra (Table 10). A clear SAR study showed that the change in the chirality of Pro ring does not affect the activity.…”
Section: Medicinal Chemistry Efforts Toward the Development Of Novel ...mentioning
confidence: 99%
“…Multi‐drug resistance (MDR) and extensive‐drug resistance (XDR) are growing problems and are fueling the tuberculosis epidemics [36,37] . According to this the development of new compounds being active against M. tuberculosis is relevant [38–45] . A drug screening with M. tuberculosis is hampered with slow growth rate and special working conditions required for making the experiment safe.…”
Section: Introductionmentioning
confidence: 99%
“…[36,37] According to this the development of new compounds being active against M. tuberculosis is relevant. [38][39][40][41][42][43][44][45] A drug screening with M. tuberculosis is hampered with slow growth rate and special working conditions required for making the experiment safe. Thus, the use of non-pathogenic and fast-growing mycobacterium as a model organism is a good starting point for possible drug search.…”
Section: Introductionmentioning
confidence: 99%
“…The Gewald aminothiophene fragment is a promising pharmacophore group, since it was found in both natural and synthetic physiologically active compounds [1][2][3][4][5][6]. The synthesis of substituted Gewald aminothiophenes can be carried out using the Gewald reaction [7][8][9].…”
Section: Introductionmentioning
confidence: 99%